2014
DOI: 10.1002/14651858.cd004734.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and/or heparin for women with unexplained recurrent miscarriage with or without inherited thrombophilia

Abstract: There is a limited number of studies on the efficacy and safety of aspirin and heparin in women with a history of at least two unexplained miscarriages with or without inherited thrombophilia. Of the nine reviewed studies quality varied, different treatments were studied and of the studies at low risk of bias only one was placebo-controlled. No beneficial effect of anticoagulants in studies at low risk of bias was found. Therefore, this review does not support the use of anticoagulants in women with unexplaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
121
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 95 publications
4
121
0
8
Order By: Relevance
“…16 Thus, conclusive data were still lacking concerning the effect of LMWH alone in improving the outcome of pregnancy in women with unexplained recurrent miscarriage. This is supported by the last meta-analysis 23 in which the authors state that only the data of 6 patients 22 could be The women included in the per-protocol analysis were treated at least 7 days until loss or beyond 12 weeks' gestation, and the injections were started before 6 weeks' gestation or at least 1 week before the most advanced term reached before during previous pregnancies. Congenital abnormality*, n (%) 7 (5) 3 (2.5) .35…”
Section: Discussionmentioning
confidence: 93%
“…16 Thus, conclusive data were still lacking concerning the effect of LMWH alone in improving the outcome of pregnancy in women with unexplained recurrent miscarriage. This is supported by the last meta-analysis 23 in which the authors state that only the data of 6 patients 22 could be The women included in the per-protocol analysis were treated at least 7 days until loss or beyond 12 weeks' gestation, and the injections were started before 6 weeks' gestation or at least 1 week before the most advanced term reached before during previous pregnancies. Congenital abnormality*, n (%) 7 (5) 3 (2.5) .35…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the recent Cochrane review suggests that the live birth rate is not affected by LMWH treatment in unexplained RM patients [14]. In opposition to that stands a recent study from Turkey reporting positive effects of LMWH on live birth rate in recurrent miscarriage patients who used LMWH when compared to patients without LMWH treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…In recent Cochrane meta-analysis the authors did not recommend anticoagulants in RM patients beyond those complicated with inherited thrombophilia. They also suggested that pregnancy complications like preterm delivery, preeclampsia, IUGR and congenital abnormalities were not significantly affected by the use of aspirin or LMWH [14]. Despite this, empirical therapy for unexplained RM patients in form of a low dose aspirin and prophylactic doses of LMWH has been a widespread clinical practice in several clinics around Turkey [15].…”
Section: Introductionmentioning
confidence: 99%
“…В то же время систематический обзор P. de Jong и соавт. [21] не подтвердил эффективность применения низкомолеку-лярных гепаринов и/или антиагрегантов в снижении ча-стоты развития акушерских осложнений у женщин с не-объяснимым повторным невынашиванием беременности (имеющих или не имеющих врожденную тромбофилию), но авторы отмечают, что необходимо проведение даль-нейших хорошо организованных рандомизированных контролируемых исследований.…”
unclassified
“…Беременность в норме является гиперкоагу-ляционным состоянием, но чрезмерная гиперкоагуляция способствует развитию осложнений, в том числе тяжелой ПЭ [21]. Поэтому патогенетически оправданным является применение гепарина, но действие его не ограничивается антикоагулянтным эффектом.…”
unclassified